2015
DOI: 10.1016/j.jse.2014.06.048
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin reduces fibrosis and protects against muscle weakness after massive rotator cuff tear

Abstract: Background Chronic rotator cuff tears are a common source of shoulder pain and disability, and patients with chronic cuff tears often have substantial weakness, fibrosis, inflammation and fat accumulation. Identifying therapies to prevent the development of these pathologies will likely have a positive impact on clinical outcomes. Simvastatin is a drug with demonstrated anti-inflammatory and anti-fibrotic effects in many tissues, but had not previously been studied in the context of rotator cuff tears. We hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 42 publications
(71 reference statements)
1
25
0
Order By: Relevance
“…We suspect that ECM gene expression levels for both VML and isolated DSM groups were elevated during earlier time points; an expression pattern that is consistent with muscle fibrosis. 43 Once a stable fibrotic scar was formed, the genes returned to the lower expression values we measured at 12 weeks. It is also important to note that the collagen I immunoreactivity and PCR analysis were conducted on samples taken from different tissue regions.…”
Section: Decellularized Skeletal Muscle With Minced Muscle Autograftsmentioning
confidence: 81%
“…We suspect that ECM gene expression levels for both VML and isolated DSM groups were elevated during earlier time points; an expression pattern that is consistent with muscle fibrosis. 43 Once a stable fibrotic scar was formed, the genes returned to the lower expression values we measured at 12 weeks. It is also important to note that the collagen I immunoreactivity and PCR analysis were conducted on samples taken from different tissue regions.…”
Section: Decellularized Skeletal Muscle With Minced Muscle Autograftsmentioning
confidence: 81%
“…It is postulated that increased fibrosis results in higher tension in the muscle in RC tears, thus making repair more challenging in chronic, retracted tears. In a clinical setting, fibrosis has been found in human RC tissue at time of repair and has been correlated with decreased force production and increased disruption of myofibril architecture 6,[22][23][24] . Fibrosis has also been identified as a direct cause of muscle dysfunction in muscular dystrophy.…”
Section: @ C I C E D I Z I O N I I N T E R N a Z I O N A L Imentioning
confidence: 99%
“…Poor outcomes and high re-tear rates after surgery are thought to be due in part to these changes within the muscles 1 , and have been demonstrated to directly correlate with the amount of muscle atrophy and FI [2][3][4][5] . Although fibrosis is not well described in RC injuries, recent studies have linked poor muscle function to increased expression of fibrotic markers following RC injury 6,7 . Fibrosis is also found after other muscle injuries and has been shown to directly cause muscle dysfunction in muscular dystrophy.…”
Section: Introductionmentioning
confidence: 99%
“…6) SV is one of the statins, which are widely used as medication for treating hypercholesterolemia and cardiovascular diseases. In addition, it was reported that the active form of SV, simvastatin hydroxy acid (SV-acid), 7) partially protected against muscle weakness after massive rotator cuff tear in rats, 8) affected the expression of heme oxygenase-1 in mice 9) and inhibited the induction of matrix metalloproteinase-9 in rats. 10) Moreover it had an antiinflammatory action and promoted epithelial cell proliferation.…”
mentioning
confidence: 99%